Oral and System Health: Real Collaboration for Innovations in Healthcare and Policy (Bangladesh Journal of Medical Science, 2023)
This editorial mainly focuses on the implementing Oral and Systemic health in the personal healthcare system to improve the patient care. It provides proper method of implementing the Systemic health in the healthcare care sector and also has been shown different approach that is beneficial to adopt the method of Transdisciplinary science and different healthcare policy in the healthcare sector. Moreover, this report also shaded light on the different result that is faced by the healthcare sector after implementing the role of Systemic health in the Oral healthcare sector. Further, this article also provided different opinion of effects of the Systemic health in the Oral health.Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.1-3